Sulphated and unsulphated bile acids in serum, bile, and urine of patients with cholestasis. Issue 11 (November 1976) - van Berge Henegouwen, G P; Brandt, K H; Eyssen, H; Parmentier, G
Abstract : Samples of serum, bile, and urine were collected simultaneously from patients with cholestasis of varying aetiology and from patients with cirrhosis; their bile acid composition was determined by gas/liquid chromatography and mass spectrometry. In cholestasis, the patterns in all three body fluids differed consistently and strikingly. In serum, cholic acid was the major bile acid and most bile acids (greater than 93%) were unsulphated, whereas, in urine, chenodeoxycholic was the major bile acid, and the majority of bile acids (greater than 60%) were sulphated. Secondary bile acids were virtually absent in bile, serum, and urine. The total amount of bile acids excreted for 24 hours correlated highly with the concentration of serum bile acids; in patients with complete obstruction, urinary excretion averaged 71-6 mg/24 h. In cirrhotic patients, serum bile acids were less raised, and chenodeoxycholic acid was the predominant acid. In healthy controls, serum bile acids were consistently richer in chenodeoxycholic acid than biliary bile acids, and no bile acids were present in urine. No unusual monohydroxy bile acids were present in patients with primary biliary cirrhosis, but, in several patients, there was a considerable amount of hyocholic acid present in the urinary bile acids. The analyses of individual bile acids in serum and urine did not appear to provide helpful information in the differential diagnosis of cholestasis. Thus, in cholestasis, conjugation of chenodeoxycholic acid with sulphate becomes a major biochemical pathway, urine becomes a major route of bile acid excretion, and abnormal bile acids are formed.